Evaluation of Intraocular Lens Tilt and Decentration in Congenital Ectopia Lentis by the Pentacam Scheimpflug System. (11th March 2022) - Ye, Huiwen; Liu, Zhenzhen; Cao, Qianzhong; Lian, Zhangkai; Zhang, Xinyu; Zheng, Danying; Jin, Guangming
Abstract : Purpose . The purpose of this study was to quantify the characteristics of the tilt and decentration of the IOL after trans-scleral suture fixation surgery in congenital ectopia lentis (CEL) patients. Methods . The clinical characteristics of 70 CEL patients at Zhongshan Ophthalmic Center in China were retrospectively analyzed. The tilt and decentration of intraocular lens (IOL) were measured by using a Pentacam and compared between different axial length (AL) subgroups. The correlation between IOL tilt, decentration, and ocular characteristics was investigated using Spearman's correlation analysis. Results . The postoperative IOL position of CEL patients was mainly located nasally inferiorly. The average tilt of the IOL in CEL patients was less than 7° (for temporal: 2.21 ± 1.53°, for nasal: −1.84 ± 2.04°, for superior: 2.22 ± 2.18°, and for inferior: −1.70 ± 1.62°), and the average decentration of the IOL in CEL patients was larger than 0.4 mm (for temporal: 0.49 ± 0.38 mm, for nasal: −0.69 ± 0.46 mm, for superior: 0.72 ± 0.58 mm, and for inferior: −0.68 ± 0.54 mm). The decentration of CEL patients in the AL ≥ 26 subgroup was greater than those with AL < 24 mm and AL 24 to 26 mm subgroups (for superior: 0.72 ± 0.28 mm vs. 0.46 ± 0.25 mm and 0.48 ± 0.22 mm, all P < 0.05 ; for inferior: -0.94 ± 0.56 mm vs. −0.44 ± 0.26 mm and -0.44 ± 0.46 mm, all P < 0.05 ). IOL decentration was positively correlated with AL (for superior: r  = 0.44, P = 0.019 ; for inferior: r  = 0.54, P = 0.006 ). IOL tilt was positively correlated with AL on the superior side ( r  = 0.38, P = 0.041 ). Conclusions . The extent of IOL decentration after trans-scleral suture fixation was great in CEL patients, and the IOL decentration in CEL patients was significantly associated with AL.